2020
DOI: 10.3346/jkms.2020.35.e290
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Factors of Transportation Costs regarding Healthcare Service Utilization in Korea

Abstract: Background: Transportation costs can be a barrier to healthcare services, especially for low-income, disabled, elderly, and geographically isolated populations. This study aimed to estimate the transportation costs of healthcare service utilization and related influencing factors in Korea in 2016. Methods: Transportation costs were calculated using data from the 2016 Korea Health Panel Study. A total of 14,845 participants were included (males, 45.07%; females, 54.93%), among which 2,148 participants used inpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Unmet healthcare needs were measured as "yes" replies to the question, "Have you ever missed seeing a doctor or getting a medical checkup that was necessary during the last year?" referring to previous literature (32,33).…”
Section: Dependent Variablesmentioning
confidence: 87%
See 1 more Smart Citation
“…Unmet healthcare needs were measured as "yes" replies to the question, "Have you ever missed seeing a doctor or getting a medical checkup that was necessary during the last year?" referring to previous literature (32,33).…”
Section: Dependent Variablesmentioning
confidence: 87%
“…Surveys were conducted annually on all eligible household members using the computer-assisted personal interviewing technique. The KHP provides information on health conditions, unmet needs, healthcare utilization, socioeconomic characteristics, and demographic characteristics and has been used to analyze unmet needs and healthcare utilization (32,33).…”
Section: Data Source and Participantsmentioning
confidence: 99%
“…This study examined only out-of-pocket expenses of health insurance, but receiving treatment in a different region involves additional costs for transport and the accompanying caregiver (if any) and additional time, doubling the total costs. 28 If local residents travel to other regions to receive essential medical services because there is no reliable healthcare delivery system in the residential region, such additional costs are incurred by them alone. Therefore, the total medical expenses spent in other regions can help estimate the costs that can be saved by building a local healthcare delivery system that ensures essential medical services.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the transportation cost burden on people living in rural areas and low-income populations are higher. Therefore, patients in these vulnerable groups carry a double burden from cancer [31]. Studies on treatment outcomes in settings where all patients with cancer receive equal access to treatment and supportive care confirmed that similar treatments yield similar outcomes [28,29].…”
Section: Discussionmentioning
confidence: 99%